Artisans in a Merchant Town: St.John’s, Newfoundland, 1775-1816 - Cadigan, Sean (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1993)
AbstractArtisans who specialized in the production of consumer goods in St. John's during the American Revolutionary and Napoleonic eras became neither proletarians nor industrial capitalists as historiography suggests was the fate of others in the Anglo-American world. While limited proletarianization was important among carpenters, and merchant credit dominated artisans in maritime trades, some producers of consumer goods made the transition from artisan to merchant. Evidence drawn from court records, newspapers and government correspondence suggests that some St. John's artisans found greater opportunities in building on the accounting and trading skills they acquired from the retail and importing aspects of their trade rather than in manufacturing as such. Mercantile activity rather than manufacture offered the best chance for capital accumulation in an economy characterized by the resource and structural impediments of monostaple production.